'Protect the Brisbane backyard!' (Except from subdivision for additional house construction). Issue 4 (2nd October 2020) - Gallagher, Rachel; Sigler, Thomas; Liu, Yan
ABSTRACT: Greyfield infill has been widely pursued as a neoliberally guided consolidation policy favouring high amenity, higher density redevelopments in existing residential areas. In the context of rapidly transforming inner-city suburbs, the question becomes whether consolidation can be achieved through laissez faire zoning combined with strong market incentives for both large- and small-scale developers. This study draws upon an empirical analysis of property boundary change in Brisbane, Australia to demonstrate that without adequate specification, consolidation policy encouraging infill of greyfield inner-city sites can create perverse outcomes that fragment, rather than consolidate, the existing lot structure. The creation of 'backyard subdivisions' is one outcome in which additional dwellings are built alongside existing houses protected by preservationist statutes. Despite best intentions to retain dwelling character whilst consolidating growth, redevelopment outcomes do not achieve the purported benefits of consolidation. Clear planning controls are required if greyfield infill is to play a role in halting peripheral urban expansion.